Моделирование переходных процессов в трехфазном трансформаторе с учетом топологии и гистерезисных свойств магнитопровода - Зирка, С.Е.; Мороз, Ю.И.; Мороз, Е.Ю.; Тарчуткин, А.Л. (Технічна електродинаміка, 2011)
The algorithm for determining equivalent circuit parameters and a model of three-phase five-legged transformer are proposed. The model takes account the hysteretic and dynamic properties of the core material and reproduces magnetic fluxes in the nonmagnetic medium. The applicability of the model in studying main transformer regimes is shown.